PENERAPAN MEDIA PEMBELAJARAN BERBASIS PERMAINAN MONOPOLI EMOSI UNTUK MEMBANDINGKAN KECERDASAN EMOSIONAL SISWA-SISWI SDN MARGAMULYA - Gian Rusdiyana; Maulida Putri; Desi Setiyadi; Putri Nurina; Aceng Akhmad Munanzdar Alkafi Billah (Fakultas Tarbiyah dan Keguruan, 2025)
This community service activity aims to improve and compare emotional intelligence between students and students at SDN Margamulya through the implementation of innovative learning media in the form of the Emotional Monopoly game. This media is the work of Fikri Suhardi, a Guidance and Counseling teacher as well as a content creator who focuses on children's character education. The game is designed to help learners recognize, understand, and manage their emotions in a fun and interactive way. The method used in this activity is a quantitative approach with a simple experimental design. Data was collected through emotional intelligence measurement instruments before and after the implementation of the game, then analyzed using an independent sample t-test to determine the significant differences between groups of students and students. The results of the analysis showed that there was a significant difference between the emotional intelligence of students and students after participating in this activity. The average emotional intelligence score of female students reached 7.90, while students obtained an average of 6.50. These findings indicate that female students have a higher and more stable level of emotional intelligence than students after participating in the Emotional Monopoly game. This activity not only contributes to improving the emotional aspects of students, but also shows the great potential of educational game media as an effective means of social-emotional learning at the elementary school level. Therefore, it is recommended that similar games can be integrated more widely in learning activities and guidance and counseling services in schools.